The Influence of Brand Ambassadors on Purchase Decisions: The Mediating Role of Electronic Word of Mouth and the Moderating Effect of Brand Image in the Indomie Market - Dede Farida; Latifah Ayu Tiarani; Lita Aliyyusia; Septiana Dewi; Tiara Maharlica Puteri Amalia (Lentera Ilmu Nusantara, 2025)
This study explores the influence of Brand Ambassadors on purchase decisions of Indomie products, with Electronic Word of Mouth (E-WOM) as a mediating variable and brand image as a moderating variable. The objective is to examine how Brand Ambassadors affect purchasing decisions both directly and indirectly through E-WOM, and to what extent brand image strengthens this relationship. A quantitative approach was employed, with data collected through questionnaires from 103 respondents and analyzed using SmartPLS 3 software. The results show that Brand Ambassadors have a significant influence on E-WOM, but not directly on purchase decisions , suggesting that digital word-of-mouth serves as a critical transmission channel through which endorsement effects are converted into consumer action. However, E-WOM and brand image significantly mediate and moderate the relationship, demonstrating that consumer-generated digital interactions and brand perceptions jointly shape purchasing behavior in high-frequency consumption markets. In conclusion, E-WOM strengthens the influence of Brand Ambassadors on purchase decisions, and brand image reinforces this relationship, highlighting the importance of an integrated digital marketing strategy while also contributing to digital marketing and consumer behavior theory by clarifying the indirect and conditional pathways through which endorsement influences operate in FMCG settings.